Lactylation: the metabolic–immune hub in autoimmune diseases - Xia, Qingqing; Sun, Dantong; Wan, Ke; Liu, Chengcheng; Shu, Han; Wang, Miao; Zhou, Tongsheng; Chen, Ying; Yang, Xue; Li, Xiao-Feng; Song, Biao; Wang, Facai (Frontiers in Immunology, 2025)
In recent years, lactate modification, as an emerging post-translational modification mechanism, has attracted increasing attention for its role in the regulation of the immune system. Autoimmune diseases are a category of complex disorders characterized by abnormal attacks of the immune system on self-tissues. The limitations of traditional treatments have made the search for new therapeutic targets a hot topic in research. Lactate modification plays a significant role in the development and progression of autoimmune diseases. It can modulate the activation and function of T cells, B cells, macrophages, and dendritic cells, thereby influencing inflammatory and autoimmune responses. In diseases such as experimental autoimmune uveitis (EAU), rheumatoid arthritis (RA), and systemic lupus erythematosus (SLE), lactate modification is closely related to disease progression and can exert its effects by regulating key signaling pathways and cytokine networks. Research on lactate modification as a therapeutic target has also made certain progress, providing new ideas for the treatment of autoimmune diseases. However, there are still many challenges to be faced, such as the development of specific inhibitors, the evaluation of potential side effects, and the feasibility of clinical application. The important regulatory role of lactate modification in autoimmune diseases offers a new target for treatment. Future research needs to further explore its specific mechanisms in the immune system, optimize therapeutic strategies, and assess its clinical application prospects, in order to bring breakthrough progress to the treatment of autoimmune diseases.